THE PROCESSING LOAD AND THE DYNAMISM OF THE PROCEDURAL STANDARD - Adrián Calvinho, Gustavo (2017)
The procedural charges that arise as activities of the parties in the jurisdictional process become like the original gender of the burden of proof; these are in the conceptualization of the thoughts of Goldschmidt and Carnelutti. The doctrine has treated procedural charges by basing the part of the discussion itself and is a faculty of an obligation; however, the controversy arises from the observation  of the dynamics of the procedural norm and its structure, from which arises the consecutive character that generates the conduct of each one of the parties. It is precisely this dynamism that allows the party to opt for a positive behavior of the omission in which the right to defense in the trial materializes